Experience of using internal fixation in the treatment of patients with inflammatory complications of mandibular fractures: a retrospective study - Alexander S. Pankratov; Zauri P. Gotsiridze; Mariya A. Karalkina (Russian Open Medical Journal)
Study goal — To evaluate the efficacy of plate osteosynthesis in the treatment of patients with inflammatory complications of mandibular fractures on a large sample. Material and Methods — We conducted a retrospective analysis of medical records collected over 15 years in a group of patients with inflammatory complications of mandibular fractures. The analysis included medical records of patients who underwent plate osteosynthesis operations performed according to the surgical algorithm adopted in the clinic, in combination with a simultaneous directed antibacterial effect on the microflora of the pathological focus and osteoplastic replacement of defects. We identified 164 medical records meeting the search criteria distributed among two study groups. Group A included hospitalized patients with developed abscesses and phlegmons of soft tissues surrounding the fracture area. For them, two-stage surgical intervention was performed. Group B consisted of patients who had no suppurative process in soft tissues, which allowed them undergoing one-stage surgical treatment. Results — Good, satisfactory, and unsatisfactory surgical outcomes were obtained in 82.6%, 14.9%, and 2.4% of the patients, respectively. The differences between the comparison groups were not statistically significant. Conclusion — The clinical effectiveness of an integrated approach to the surgical treatment of patients with inflammatory complications of mandibular fractures, based on providing stable fixation of connected fragments as a critical factor in bone wound healing via osteosynthesis, was confirmed on large samples in both comparison groups.